2008
DOI: 10.1093/europace/eun071
|View full text |Cite
|
Sign up to set email alerts
|

Long-term endurance sport practice increases the incidence of lone atrial fibrillation in men: a follow-up study

Abstract: Long-term endurance sport practice is associated with a higher risk of symptomatic LAF in men. This risk is associated with a larger left atrial inferosuperior diameter and volume in physically active subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
2
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 286 publications
(198 citation statements)
references
References 28 publications
7
179
2
10
Order By: Relevance
“…29,31,54 Indeed, long-term sustained vigorous aerobic ET such as marathon or ultramarathon running or professional cycling has been associated with as much as a 5-fold increase in the prevalence of atrial fibrillation. 19,30,31,37,[55][56][57][58][59][60][61][62][63] Potential mechanisms underlying the association of long-term excessive exercise and atrial fibrillation are speculative but may include increased vagal and sympathetic tone, bradycardia, inflammatory changes, atrial wall fibrosis, and increased atrial size. 59 Some data indicate that atrial size may be larger in veteran endurance athletes than in age-matched sedentary controls.…”
Section: Proarrhythmic Effects Of Excessive Endurance Etmentioning
confidence: 99%
“…29,31,54 Indeed, long-term sustained vigorous aerobic ET such as marathon or ultramarathon running or professional cycling has been associated with as much as a 5-fold increase in the prevalence of atrial fibrillation. 19,30,31,37,[55][56][57][58][59][60][61][62][63] Potential mechanisms underlying the association of long-term excessive exercise and atrial fibrillation are speculative but may include increased vagal and sympathetic tone, bradycardia, inflammatory changes, atrial wall fibrosis, and increased atrial size. 59 Some data indicate that atrial size may be larger in veteran endurance athletes than in age-matched sedentary controls.…”
Section: Proarrhythmic Effects Of Excessive Endurance Etmentioning
confidence: 99%
“…Low-level vagal stimulation prevents AF by decreasing sympathetic and parasympathetic cardiac responsiveness in animal models susceptible to AF 74 . High-intensity endurance training is an evolving risk factor underlying AF in middle-aged Europeans without overt structural heart disease 75,76 , which can be mediated by an elevated parasympathetic tone, structural changes, or by changes in ion-channel expression 14,73,77 . Similarly, AF in patients with obstructive sleep apnoea can be provoked by autonomic imbalance 14,78 .…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…6,[8][9][10][11][12][13][14][15] Furlanello et al 16 and Pelliccia et al 17 reported a low rate of AF (0.2 % and 0.3 %, respectively), no different from that observed in the general population. However, both studies included exclusively young athletes with relatively fewer years of training.…”
Section: Prevalence and Incidence Of Atrial Fibrillation In Endurancementioning
confidence: 91%